2017
DOI: 10.14689/ejer.2017.67.8
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Maternal Emotion Socialization Behaviors, Children’s Self‐ Perceptions, and Social Problem‐Solving Skills 

Abstract: In 2017 and 2018, engineering applications and design process were given weight to with the updates carried out in the Physical Sciences Lesson Curriculum in Turkey. For the STEM education which is at the center of this update to reach its target, it is highly important that students accurately learn what engineers do, what their work field is, the characteristics they should carry and understand the nature of engineering. The present study aims to identify the perception of engineers of 5th, 6th and 7th grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Accordingly, it can be stated that how a person perceives oneself directly affects their competence to communicate with others. This finding is consistent with other studies in the relevant literature on self-concept and communication skills (Gizir & Baran, 2003;Ozkan, 2015;Polat & Aksin, 2015;Sarason & Sarason, 1986;Schroeder, 1995). The main purpose of this study was to examine how self-compassion is positioned in the relation between these two variables.…”
Section: Conclusion and Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Accordingly, it can be stated that how a person perceives oneself directly affects their competence to communicate with others. This finding is consistent with other studies in the relevant literature on self-concept and communication skills (Gizir & Baran, 2003;Ozkan, 2015;Polat & Aksin, 2015;Sarason & Sarason, 1986;Schroeder, 1995). The main purpose of this study was to examine how self-compassion is positioned in the relation between these two variables.…”
Section: Conclusion and Discussionsupporting
confidence: 87%
“…Self-concept is related to social-emotional development and social problem solving (Ozkan, 2015;Polat & Aksin, 2015). Furthermore, it is stated that self-esteem, which can be considered as a sub-dimension of selfconcept, is positively related to social behaviour (Gizir & Baran, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, it significantly increases understanding, performance and attitudes during mathematics classes (Albay, 2019). There is a relationship between attitude and social problem-solving skills (Ozkan & Aksoy, 2017;Salehudin, Hamid, et al, 2020).…”
Section: Simultaneous Relationship Between Predictor Variables and Prmentioning
confidence: 99%
“…On the other hand, parents' negative communication and non-supportive reactions such as strict parental behavior, punishment or stress in parents affect their communication with their children negatively. Studies examining the effects of mothers on their children's socialization have found a positive relationship between mothers' emotional supportive reactions and their children's social competence skills (Bayindir, Guven, Sezer, Aksin-Yavuz & Yilmaz, 2017;Ozkan & Aksoy, 2017). Various perspectives emphasized that children's social competence skills are based on their relationship with their fathers.…”
Section: Children's Social Competence Levels and Their Parents' Communication With Themmentioning
confidence: 99%